THE ROLE OF PELABUHAN PERIKANAN NUSANTARA SIBOLGA TOWARD THE RURAL LABOR ABSORPTION IN PONDOK BATU VILLAGE, SARUDIK DISTRICT, CENTER TAPANULI REGENCY, NORTH SUMATERA PROVINCE - Yohannes A Banjarnahor; Eni Yulinda; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conductded on January 2016 in Pondok Batu Village, Sarudik District, Center Tapanuli Regency, North Sumatera Province. This research purposed were to analyze the role of Pelabuhan Perikanan Nusantara Sibolga in fisheries industry development toward the local rural labor absorption, and to analyze percentage of Pelabuhan Perikanan Nusantara Sibolga contribution toward the local rural labor absoption in Pondok Batu Village. The method used in for this research was observation case study method and respondent determining with purposive sampling.The result indicated, that in Pelabuhan Perikanan Nusantara Sibolga industry development has been make into Pondok Batu Village being the center of fisheries industry in Center Tapanuli and increase the people economy. Pelabuhan Perikanan Nusantara Sibolga contribution toward local rural labor absorption as 872 or 51,23 % rural labor, and total rural labor as much as 2856 person.Keyword : The Role, Sibolga, Pelabuhan Perikanan Nusantara Sibolga, Rural Labor Absorption, Pondok Batu Village.